Lubao Bamboo Hub a processing and research center for engineered bamboo - Manguray, Alarice Ann F.; Perion, Sharon S. (Quezon City College of Architecture, University of the Philippines, Diliman, 2018)
Known to be the Cradle of Kapampangan Civilization and the largest municipality on Pampanga, Lubao has become the center of agriculture in the province. Because of its geophysical characteristics, Lubao is describes as a low-lying land transverse by narrow streams and rivers that contributes to the lands problem in soil erosion. With this, the local government initiated the bamboo plantation along riverbanks as a long-term response to protect and strengthen areas along streams and rivers. The local government of Lubao's commitment and desire in promoting environmental sustainability is fueled by their vision to promote bamboo as a very important plant and alternative material to commercial lumber. The proposed project, Lubao Bamboo Hub, is a research and processing facility that would serve the main agenda of the project of promoting and boosting the local bamboo industry with following sub-agenda: educational support, economic support, and ecological support. Lubao Bamboo Hub is located across the existing Lubao Linear EcoPark where the first bamboo plantation started. The center houses retail spaces, a multi-purpose hall for congregations, processing and workshop spaces, laboratories, and an accommodation building. The development shall be a part of the whole Lubao Bamboo Hub complex which includes linear park, bamboo plantation, materials recovery facility and bamboo briquetting facility, and the river tourism development of the Town of Lubao. With the establishment of the facility, skills and knowledge in agri-industries of the locals would increase, helping them increase their opportunity for employment. The facility would also help in establishing bamboo as on of the town's main product, and would help in increasing awareness on the importance and strength of bamboo as an alternative renewable material.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Bamboo